PELAKSANAAN MUATAN LOKAL KURIKULUM ACEH PADA SMA SESUAI PERATURAN GUBERNUR ACEH NOMOR 7 TAHUN 2022 - Muhammad Yani Muhammad Yani; Safrul Muluk Safrul Muluk; Silahuddin Silahuddin; Eka Mayasari Eka Mayasari (Jurnal Pendidikan Nusantara, 2024)
Aceh Governor's Regulation (Pergub) Number 7 of 2022 is an important guideline for implementing the Acehnese curriculum related to local content (Mulok) in high school (SMA) in Aceh. This local content aims to maintain and introduce Acehnese culture to the younger generation, as well as increase the knowledge and skills of students that are relevant to the local context, in this case in accordance with Government Regulation Number 7 of 2022 specifically regarding Mulok PAI. The purpose of this research is to find out about the Mulok PAI problem policy, the strategy for increasing PAI hours, and the local content curriculum model in high school. The method used in this research uses a qualitative descriptive approach with a case study approach. Data collection techniques through observation, interviews, and documentation. The analysis technique includes stages of data collection, data reduction, data presentation, and drawing conclusions. Results The research results show that: Implementation of Mulok PAI in secondary schools in Aceh, especially in SMAN 1 Peukan Bada, SMAN 1 Darul Imarah and SMAN 10 Fajar Harapan Banda Aceh Curriculum planning, especially at SMAN 1 Peukan Bada, SMAN 1 Darul Imarah and SMAN 10 Fajar Harapan Banda Aceh have not yet prepared a mature curriculum plan, there is a gap with the national curriculum which generally uses standard content from the madrasah curriculum in accordance with the field of study in the masdrasah. The implementation of the curriculum related to the Aceh curriculum with local content is no different at all from the implementation of the national curriculum as with other subjects in schools. The evaluation of the curriculum related to the Aceh curriculum with local content is also no different at all from the implementation of the national curriculum as with other subjects in schools.